IN VITRO TESTING OF CLOVE EXTRACTS IN INHIBITING AND KILLING STAPHYLOCOCCUS AUREUS AND ESCHERICHIA COLI - Nadia Dwi Rahmawati; Tri Nur Kristina; Endang Sri Lestari; Hardian Hardian (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
Background: Diarrhea that could be caused by Staphylococcus aureus and Escherichia coli can be prevented by increasing hand hygiene using alcohol-based hand rub, but frequent use might cause skin irritation. Replacing alcohol with herbs could avoid this side effect. Cloves have been proved to have antibacterial properties. However, most researches used complex extraction methods that might not be applicable on a household scale.Objective: To prove that clove extracts have ability to inhibit and to kill S. aureus and E. coli.Methods: This is an experimental study by using post-test only control group design. Clove extract was obtained with simple aqueous maceration. Samples were Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 25922 allocated into six groups: clove extracts at concentrations of 12.5%, 25%, 50%, 100% respectively; 70% alcohol as a positive control; and aquadest as a negative control. Each group was given 5 repetitions of intervention. MIC was measured with dilution method, while MBC with streak method. Negative controls were only used to monitor the quality of this work.Results: MIC of S. aureus was started at 50% concentration of clove extract, while MBC of S. aureus was started at 25 % concentration of the same extract. MIC and MBC of E. coli was both started at 25% concentration of clove extract. MIC and MBC of 100% concentration of clove extract were equal with 70% alcohol.Conclusion: Concentration of 100% clove extracts have similar ability with 70% alcohol to inhibit and to kill S. aureus and E. coli. Keywords: Clove Extracts, Escherichia coli, MBC, MIC, Staphylococcus aureus